2009
DOI: 10.1021/jf902255h
|View full text |Cite
|
Sign up to set email alerts
|

Saponins in Yerba Mate Tea (Ilex paraguariensis A. St.-Hil) and Quercetin Synergistically Inhibit iNOS and COX-2 in Lipopolysaccharide-Induced Macrophages through NFκB Pathways

Abstract: Yerba mate tea ( Ilex paraguariensis ) is growing in popularity around the world. The objective of this study was to investigate the potential anti-inflammatory effect of yerba mate tea (MT) extracts as well as some of its phytochemicals and their interactions. MT and decaffeinated MT extracts [1-300 microM chlorogenic acid (CHA) equiv]; CHA, caffeine from MT (matein), and mate saponins (1-300 microM); quercetin (1-200 microM); and ursolic and oleanolic acids (1-100 microM) were tested by measuring their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 32 publications
5
69
0
Order By: Relevance
“…I). Previous studies reported that quercetin reduced macrophage (10)(11)(12)(13) and adipocyte ( 10 ) infl ammation through suppressing phosphorylation of c-Jun N-terminal kinase and c-Jun and inhibiting activation of NF-B. Therefore, AMPK/SIRT1 activation by quercetin might increase FA oxidation, depress infl ammatory signals such as c-Jun and NF-B, and enhance glucose uptake in adipose tissues, thereby improving adipose tissue infl ammation and insulin resistance.…”
Section: Discussionmentioning
confidence: 97%
“…I). Previous studies reported that quercetin reduced macrophage (10)(11)(12)(13) and adipocyte ( 10 ) infl ammation through suppressing phosphorylation of c-Jun N-terminal kinase and c-Jun and inhibiting activation of NF-B. Therefore, AMPK/SIRT1 activation by quercetin might increase FA oxidation, depress infl ammatory signals such as c-Jun and NF-B, and enhance glucose uptake in adipose tissues, thereby improving adipose tissue infl ammation and insulin resistance.…”
Section: Discussionmentioning
confidence: 97%
“…8) Recently published evidence has shown some beneficial effects of Mate, including antioxidant, 9) antiinflammatory, 10) antiobesity, 11) antihyperlipidemic, 12) and antidiabetic properties. 13) To our knowledge, based on pain-related experimental evidence, little is known about the potential analgesic effects of Mate.…”
Section: -7)mentioning
confidence: 99%
“…Lanzetti et al (2008) determined that yerba mate reduced acute lung inflammation in mice exposed to cigarette smoke. Recently, Puangpraphant and de Mejia (2009) investigated the potential anti-inflammatory effect of yerba mate extracts as well as some of its compound and their interactions. Quercetin was determined the most potent inhibitor of pro-inflammatory responses at a concentration 10 times lower than that of other tested compounds (Puangpraphant and de Mejia, 2009).…”
Section: Antioxidant Anti-obesity Anti-inflammationmentioning
confidence: 99%